Estratégias para produção de mudas de tomateiro utilizando paclobutrazol - Seleguini, Alexsander; De Araujo Faria Júnior, Max José [UNESP]; Benett, Katiane Santiago Silva; Lemos, Odair Lacerda; Seno, Shizuo (Universidade Estadual de Londrina, 2013)
The modern tomato production, either for fruit table production or for processing, has required quality seedlings, able to withstand environmental adversities after planting and maintaining the standard genotype productive. The aim of this study was to evaluate the effect of three concentrations of PBZ (0, 50 and 100 mg L-1) and two methods of application (seed treatment and watering seedlings) on seedling emergence and seedling production of tomato growth indeterminate. We adopted a completely randomized in a 2x3 factorial scheme with four replications. We evaluated the seedling emergence, the rate of speed of emergence, seedling height and diameter of hypocotyl and their absolute growth rate (TCA), leaf area, dry weight of shoots, roots and total, and reason leaf area (RAF). Results were subjected to analysis of variance and the mean levels of the factor methods of application compared by Tukey test at 5% and the mean levels of the factor concentrations subjected to regression analysis. The application of paclobutrazol via seedlings watering did not affect seedling emergence, significantly reduced the rate of seedling growth and, consequently, the size of the seedlings without affecting the diameter of hypocotyl, plus allow accumulation of dry roots. A concentration of 50 mg L-1 was shown to be sufficient to obtain seedlings more compact, subject to leaf area, the application via watering, beyond allowing an increase of about 37% in dry weight of roots.
Strategies for tomato seedlings production using paclobutrazol
Keywords: Growth regulator; Seedling etiolation; Solanum lycopersicum L.; Triazole